What actually happens to EU directives in the member states?: A cross-country cross-sector view on national transposition instruments - Daniela Treutlein (Center for Economic Studies and ifo Institute (CESifo), 2007)
This study empirically investigates the transposition patterns of EU directives in all 15 member states and in six major sectors of the economy with a view on analysing the political-economic reasons behind sector and national differences in the legal transposition instruments used. In particular, we model the influence of both national sector importance and governmental constellations on the ratio of primary to totally transposed EU directives. We find that government strength and net EU receipts negatively affect the ratio of primary to total transpositions. Economic sector size plays a positive significant role for primary transposition ratios. However, the direction of the effect changes if we control for other sector characteristics, i.e. sector lobbying potential and technicality.
Keywords: H11; H70; H83; K40; K33; 330; EU-Recht; EU-Wirtschaftsrecht; Public Choice; Strukturpolitik; Interessenpolitik; EU-Staaten